Long-Term Acid Rock Drainage (ARD) Mitigation in Mining Cemented Tailings under Vibration and Non-Vibration Conditions - Alsakit, Mohammed; Abugharara, Abdelsalam; Amer Aborig; Stephen Butt (Sebha University Conference Proceedings, 2025)
Acid Rock Drainage (ARD) remains a critical environmental challenge in mining, driven by the oxidation of sulphide minerals in mine tailings that can cause long-term acidification and heavy metal release. Effective, sustainable mitigation strategies are essential to minimize ecological impacts and ensure responsible mine closure. This study evaluates the long-term performance of cemented tailings backfill under different cement contents and preparation conditions, with emphasis on vibration-assisted compaction as a potential enhancement. The main objective is to determine whether vibration can improve ARD suppression while reducing cement demand. A 70-week column leach experiment was conducted using tailings blended with 2%, 4%, and 6% Ordinary Portland Cement (OPC) under vibrated (WV) and non-vibrated (NV) conditions. Weekly and biweekly monitoring of pH, electrical conductivity (EC), sulphate, and dissolved metals was carried out, supported by acid-base accounting and mineral analysis. Results show that cement content and vibration both significantly influence ARD behaviour. Vibrated samples maintained more stable neutral pH and lower EC, with 4% OPC + vibration performing as well as or better than 6% OPC without vibration. Control samples with no cement exhibited severe acidification and high EC. These findings highlight vibration-assisted compaction as a cost-effective and environmentally responsible approach for ARD mitigation in underground mining.